Algorithm of Random Start Phase Correction and Frequency Offset in the Communication System with the Quadrature Modulation - A. L. Matiouchkov; I. N. Zhuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The goal of the work is to find a solution, realization, and modelling of the algorithm for the compensation of a start random phase error of a quadrature signal, which began at the input of the receiver’s digital part. This algorithm also solves the problem of carrier frequency error offset. These errors have enough values for the lock-band of Costas PLL using minimum hardware resources. To complete this task, the realization and modelling algorithm problems of phase and frequency offset error corrections in Matlab Simulink IDE, arising from Costas PLL, were solved. This algorithm sets values errors for Costas PLL work stability. From the results of calculation and modelling obtained in the article, it follows that the developed model of the receiving path completely eliminates the probability of the error of a random initial phase and frequency offset in the receiver model of a QPSK signal, before the PLL loop is switched on, which significantly reduces the time of readiness for operation of this model.